104k views
3 votes
For a given function ƒ(x) = x2 – x + 1, the operation –ƒ(x) = –(x2 – x + 1) will result in a

A) reflection across the x-axis.

B) horizontal shrink.

C) reflection across the y-axis.

D) vertical shrink.

2 Answers

2 votes

Answer:

A) reflection across the x-axis.

Step-by-step explanation: I took the test

User Peterdk
by
5.0k points
3 votes

Given:

The function is:


f(x)=x^2-x+1

To find:

The result of the operation
-f(x)=-(x^2-x+1).

Solution:

If
g(x)=-f(x), then the graph of f(x) is reflected across the x-axis to get the graph of g(x).

We have,


f(x)=x^2-x+1

The given operation is:


-f(x)=-(x^2-x+1)

So, it will result in a reflection across the x-axis.

Therefore, the correct option is A.

User Jobelle
by
5.4k points